Design and Build an Internet of Things (IoT) Based Wastewater Monitoring System at Cirebon Pelabuhan Hospital - Muhaimin, Muhammad; Dony, Abdul Rochman; Juhaeriyah , Juju (Devotion : Journal of Research and Community Service, 2025)
Wastewater at the Cirebon City Port Hospital that is not treated properly can cause environmental damage. In this case, technological advances are very rapidly developing in the manufacture of sophisticated tools, namely tools that can work automatically and have high precision. Therefore, in this study, we will conduct a prototype for monitoring the Wastewater Management Installation (WWTP), so hereby the author develops his research by directly applying the Wastewater Management Installation (WWTP) at Cirebon Port Hospital. In this prototype we used an esp 8266 microcontroller to read commands, a turbidity sensor to measure water turbidity, a DS18B20 sensor to measure the temperature of the water, a pH sensor to measure the acidity level of the water and an MIT App to read the output that is read by the sensor input that has been read by the firebase in real-time. The calibration results showed that all sensors were able to read the values with fairly good accuracy. The pH sensor shows an average accuracy of about 97.8%. The turbidity sensor shows an average accuracy of about 97.1%. The temperature sensor DS18B20 shows an average accuracy of about 97.7%. In the test results of the samples from the 4 readings in tubs 1 to 3, an error was shown because the results of the turbidity sensor reading were above 30 because the 1 to 3 tubs had not been filtered.